Why intracontinental basins subside longer: 3‐D feedback effects of lithospheric cooling and sedimentation on the flexural strength of the lithosphere. Issue 5 (3rd May 2016) - Cacace, M.; Scheck‐Wenderoth, M.
Abstract: The aim of this study is to reevaluate the character and evolution of the large‐scale subsidence of intracontinental basins using 3‐D thermomechanical numerical simulations accounting for the coupling between sedimentation, rheology‐dependent lithospheric flexure, and thermal contraction by lithospheric cooling. The flexural rigidity of the lithospheric plate is controlled by elastic‐brittle‐plastic rheology, enabling the computation of thermal and mechanical feedback processes occurring during basin subsidence. Numerical results show that depending on the sediment loading history, a rheological stratified lithosphere can subside over geological time scales without imposition of ad hoc geometric and kinematic initial conditions. Three‐dimensional feedback effects of sedimentation on the thermomechanical structure of the plate result in a weakened lower crust mechanically decoupled from the underlying mantle and therefore easily reactivated even under low background stresses. Our results explain the first‐order characteristics of the subsidence in intracontinental basins and reconcile basic observations of their deformation history. Key Points: Unravel first‐order aspect of intracontinental basin evolution Highlight the limitations of 1‐D/2‐D approaches